2008
DOI: 10.4143/crt.2008.40.4.178
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Factors Related to Suspected Second Primary Lung Cancer Development in Patients with Head and Neck Cancer

Abstract: Purpose: The rate of second primary lung cancer development for patients with head and neck cancer (HNC) has been noted. The aim of our study was to evaluate the incidence and clinical features of suspected second primary lung cancer that developed in patients with primary HNC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…Most second primary lung cancers occur synchronously within 24 months to index head and neck cancer [ 7 ]. Oro-hypopharynx or larynx are the most common sites of index head and neck tumor and ‘squamous cell’ is the most common histological type of index head and neck tumor associated with second primary lung cancer development [ 8 ]. Supraglottic laryngeal cancer is more commonly associated with second primary lung cancer as compared to glottic cancer [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most second primary lung cancers occur synchronously within 24 months to index head and neck cancer [ 7 ]. Oro-hypopharynx or larynx are the most common sites of index head and neck tumor and ‘squamous cell’ is the most common histological type of index head and neck tumor associated with second primary lung cancer development [ 8 ]. Supraglottic laryngeal cancer is more commonly associated with second primary lung cancer as compared to glottic cancer [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Screening for lung cancer by CT scan has a higher detection rate as compared to chest X-rays [ 13 , 14 ]. Chest CT or PET-CT scan should be used for early detection of second primary lung cancer, especially if the site of head and neck carcinoma are the oro-hypopharynx or larynx, if the cell type is squamous cell carcinoma, and if initial chest X-ray findings are abnormal [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…1,4,7,15 The goal of PNAM is to align the alveolar cleft segments and to correct nasal cartilage and soft-tissue asymmetry. In a long-term study, Maull et al 16 compared the effects of PNAM on the nasal shape in patients with UCLP. This study found that patients who had nasal molding in conjunction with alveolar molding maintained increased long-term nasal symmetry in comparison to those patients who underwent only alveolar molding.…”
Section: Discussionmentioning
confidence: 99%
“…Other modern techniques such as sentinel node biopsy or positron emission tomographyYCT could be useful in this regard. 16 The second key point is that, when we are dealing with synchronous cancers, there may be some difficulty in deciding which one should be treated first. It is has been considered 5 that the neoplasm with the greatest potential to shorten the patient's life should take preference.…”
Section: Discussionmentioning
confidence: 99%
“…And we cannot forget how important it is in radiotherapy simulation by tomographic tests. So in this group of patients, it seems that the two tests continue to complement each other [23][24][25][26][27].…”
Section: Imaging Modalities: Weaknesses and Strengthsmentioning
confidence: 99%